Congenital unilateral absence of facial nerve with hypoplastic abducens nerve: A case report of rare Moebius syndrome - Dr. Ankur Dharmani; Dr. Sonia Kashyap; Dr. Swati Thakur; Dr. Sandesh Guleria (Pediatric Review: International Journal of Pediatric Research, 2020)
Moebius syndrome is a rare congenital neurological disorder characterized by bilateral facial and abducens nerve paralysis. The syndrome may also include involvement of the other cranial nerves and various other congenital deformities and malformations. A one-month-old male infant presented with facial asymmetry, inability to close eye, and drooling of saliva from one side of the mouth, diagnosed to have Moebius syndrome. Early diagnosis of the cases by experienced clinicians and a supportive multidisciplinary approach can help children with Moebius syndrome and prevent associated complications.